Kit for the preparation of 111In-labeled pertuzumab injection for imaging response of HER2-positive breast cancer to trastuzumab (Herceptin). (January 2015) - Lam, Karen; Scollard, Deborah A.; Chan, Conrad; Levine, Mark N.; Reilly, Raymond M.
Abstract: We previously reported that 111 In-labeled pertuzumab imaged trastuzumab (Herceptin)-mediated changes in HER2 expression preclinically in breast cancer tumors. To advance 111 In-labeled pertuzumab to a Phase I/II clinical trial, a kit was designed for preparing this agent in a form suitable for human administration. Unit-dose kits containing pertuzumab modified with 2-(4-isothiocyanatobenzyl)-diethylenetriaminepentaacetic acid (BzDTPA) were prepared that labeled to high efficiency (>90%) with 111 In and met specifications for pharmaceutical quality. The kits were stable for 4 months and the final radiopharmaceutical was stable for 24 h. Imaging studies demonstrated high and specific uptake in HER2-positive tumors in mice using this clinical kit formulation. Highlights: Kits for preparing 111 In-BzDTPA-pertuzumab were prepared which met specifications for pharmaceutical quality. The kits were stable for at least 4 months and the final radiopharmaceutical was stable for 24 h when stored at 2–8 °C. High labeling efficiency (>90%) of the kits was achieved with 111 In. 111 In-BzDTPA-pertuzumab exhibited stability in human plasma. Biodistribution and microSPECT imaging showed specific targeting of HER2-positive tumors in mice using the kit formulation.